An English Teacher’s Reflections on Supporting a Student with Autism Spectrum (ASD) in an Inclusive Classroom - Dini Nur Aini Lubis; Maslatif Dwi Purnomo (Universitas Cokroaminoto Palopo, 2026)
Supporting students with Autism Spectrum Disorder (ASD) in inclusive classrooms requires English teachers to continuously reflect on their pedagogical practices to address diverse learning needs. However, research has predominantly focused on instructional strategies and teacher preparedness, with limited attention given to teachers’ reflective experiences in supporting students with ASD in English language classrooms. This study explored an English teacher’s reflection on supporting a student with ASD in an inclusive classroom. A qualitative descriptive design was employed using a semi structured interview and classroom observation. The data were analysed through Braun and Clarke’s thematic analysis. The findings revealed four interconnected themes: developing professional understanding of students with ASD, adapting instructional support, collaborating with the shadow teacher, and implementing fair participation and assessment. The findings indicate that reflective practice enabled the teacher to make informed pedagogical decisions by continuously adapting instruction, strengthening collaboration, and creating equitable learning opportunities while maintaining common curriculum expectations. This study highlights reflective practice as a foundation for supporting students with ASD and provides practical insights for strengthening inclusive English language teaching.